Perception of medical radiation risk in Ireland: Results of a public survey. (December 2019) - Kenny, Emer; Byrne, Brenda; Lewis, Mandy; King, Deirdre M.
Highlights: MRI was perceived as using ionising radiation. Perceived limit on number of X-rays a person can have. Natural radiation perceived as lower dose than artificial radiation. Uncertainty in exposure levels from different modalities. Abstract: The Basic Safety Standards (BSS) directive 2013/59/EURATOM places a new emphasis on the practitioner and/or referrer to inform the patient of the benefits and risks associated with radiation dose. To communicate effectively, a prior knowledge of what a person comprehends is beneficial. The aim of this study was to evaluate the Irish public's current level of understanding of ionising radiation and its associated risks. We designed a survey consisting of ten multiple choice questions and asked members of the public to respond. There were 326 responses to the public survey. All survey data was collected anonymously using snowball sampling. Overall, the data collected from this survey indicates that the respondents do not have a clear understanding of radiation risks. In particular there was a misunderstanding in which modalities use ionising radiation and there was a perceived limit in the number of X-rays a person can have in a year, implying that the public have not been informed of the principle of justification. Patients must be presented with the benefits of an exam involving ionising radiation together with a clear explanation of the risks.